The orbicules and allergenic protein of African tulip tree (Spathodea campanulata P.Beauv.): a roadside ornamental plant in Malang, Indonesia - Janis Damaiyani; Yekti Asih Purwestri; Issirep Sumardi (The East Java Biological Society, 2018)
Orbicules or ubisch bodies are capable carrying specific pollen antigens which responsible for presenting allergenic activity in the atmosphere. Currently, there is no report on the orbicules and allergenic protein in African tulip tree. Thus, this research was aimed to investigate the presence of orbicules and allergenic protein in African tulip tree and to determine their potential as allergen source. The ultrastructure of orbicules were detected using Transmission Electron Microscope (TEM) and Scanning Electron Microscopy (SEM). Allergenic proteins were analyzed based on the molecular weight using SDS-PAGE. The result showed that he orbicules were present in the tapetal cells. Furthermore, the pro-orbicules were released by tapetal cells and fill the loculus before anthesis. The SDS-PAGE analysis showing several proteins with a molecular weight of 10-70 kD were detected in African tulip tree and cauld be potential as source for allergen. Protein bands with a molecular weight 55 kDa, 48 kDa, 39 kDa, and 27 kDa appear with the darkest, clearest and thickest expression of genes compared to other bands. In other species, the protein bands with molecular weight 55 kDa, 48 kDa and 27 kDa were detected as allergen. This results indicated African tulip tree could be potential for pollen allergen from ultrastructure and allergenic protein observation.